Dalmatosomatidae, a new monotypic family, and Dalmatosoma agaricum gen. et sp. nov. (Diplopoda: Chordeumatida: Craspedosomatidea) from Croatia, Balkan Peninsula - Antić, Dragan Ž.; Rađa, Tonći; Makarov, Slobodan E. (Zootaxa, 2018)
A new millipede species, Dalmatosoma agaricum gen. et sp. nov., is described from a cave in Dalmatia (Croatia). The new taxon is clearly unique among chordeumatidans in both anterior and posterior gonopod structure and shows some noteworthy habitus features. We therefore here establish a new monotypic family, viz., Dalmatosomatidae, for the given taxon and place it within the suborder Craspedosomatidea. The new family is briefly discussed and compared with all other chordeumatidans.